EVALUASI PROGRAM PUSKESMAS MAMPU PONED (PELAYANAN OBSTETRI NEONATAL EMERGENSI DASAR) DI PUSKESMAS BANGETAYU SEMARANG - Tri Susanti; Aufarol Marom (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2019)
PONED Health center is an inpatient health center that is able to provide basic emergency obstetric and neonatal services / complications at 24 hours a day 7 days a week to provide health services to pregnant women, maternity and postpartum and newborns. This research was conducted at the Bangetayu Health Center, which is one of the health center selected as the Basic Emergency Obstetrics and Neonatal Service (PONED) in Semarang City. This study aims to evaluate the implementation of the PONED Program in the Semarang Public Health Center and to find out the driving factors and obstacles to the success of the program. This type of research is a qualitative research with a descriptive approach conducted through interviews with several informants selected based on purposive technique taken directly from the source (research subject), namely informants from the Health Department of Semarang City and Bangetayu Health Center and also the people who were targeted by the Program. The results showed that the implementation of the PONED program had not been effectively influenced by human resource factors that were still lacking and not yet maximally in quantity and in quality had not received PONED training, inadequate facilities and infrastructure also communication processes between organizations and the socialization process to community that is still not optimal. The recommended advice is to optimize the role of human resources by conducting regular training, improving facilities and infrastructure to be feasible to use, increasing the process of coordination and strengthening the communication system between organizations, and also increasing optimal socialization to the community so that the distribution of programs can be done evenly.